Reactivation of a trap-boundary fault and its impacts on hydrocarbon migration and accumulation in Longkou 7 − 6 structure, Bohai Bay Basin: insights from geology, geophysics and basin modeling - Xinyu Yan; Zhenliang Wang; Deying Wang; Lei Chen; Yanfei Gao; Jiangtao Wang (Journal of Petroleum Exploration and Production Technology)
Abstract The growth of trap-boundary faults and changes in fault sealing capacity during activation may significantly affect the evolution of hydrocarbon migration and accumulation. Previous studies have often overlooked the interaction between changes in sealing capacity and the dynamic processes of hydrocarbon migration and accumulation during fault growth/activation. This study focuses on the trap-boundary fault within the Longkou 7 − 6 (LK7-6) structure, an ideal site for examining the impact of fault activity on hydrocarbon migration and accumulation. Seismic and borehole data were used to quantitatively investigate the history of fault growth and activation, as well as changes in fault-sealing capacity during reactivation. This was achieved by calculating fault throw and shale gouge ratio (SGR). Additionally, basin and petroleum system modeling (BPSM) was employed to reconstruct the dynamic evolution of hydrocarbon migration and accumulation during reactivation. The geological and geophysical studies indicate that the trap-boundary fault consists of at least three segments connected through lateral propagation. The fault experienced growth during the Paleogene, followed by a decrease in activity, and later entered a phase of neotectonic reactivation around 5.1 Ma. This reactivation of the trap-boundary fault played a dual role in hydrocarbon migration and accumulation, providing vertical pathways for migration while also causing vertical leakage. The dynamic evaluation of fault sealing capacity demonstrates that fault reactivation could alter lithological juxtapositions, thereby compromising fault seal integrity and facilitating cross-fault hydrocarbon leakage. The study enhances the understanding of the interaction between fault dynamic evaluation and hydrocarbon migration and accumulation, particularly through the integration of fault activity history and fault-sealing capacity evaluation with basin and petroleum system modeling (BPSM). This approach offers new insights into exploration strategies for fault-bound traps, representing a significant advancement over traditional static analysis.